Accumulation of heavy metals in mosses: a biomonitoring study - Macedo-Miranda, G. (Springerplus, 2016)
The metropolitan area of the Toluca Valley (MATV) extends over an area of 1208.55 km(2) and has 1,361,500 inhabitants making it the fifth highest populated area in the country and the second highest in the state. The MATV has several environmental problems, with regards to the air quality. Particles PM(10) and PM(2.5) are considered to be the main pollutant due to these particles frequently exceeding the limit laid down in the standards of the air quality in the country. For this reason, samples of the mosses Fabriona ciliaris and Leskea angustata were collected at different sites in MATV, Mexico in order to establish the atmospheric deposition of heavy metals by means of the analysis of the mosses tissues. Results show the average metal concentrations in the mosses in the order of: Zn > Pb > Cr > Cd. The concentration capacities of heavy metals were higher in Fabriona ciliaris than Leskea angustata. Enrichment factors for Cr, Zn, Pb and Cd were obtained using the soils from the same sampling area. Enrichment factors results show that Cr is conservative in both sampling seasons with a terrigenous origin; Zn is moderately enriched in both sampling seasons and mainly associated to pedological-soil or substrate contribution and anthropogenic activities and Cd is highly enriched in the rainy season and Pb is highly enriched in both sampling seasons, with a predominantly anthropogenic origin. This study provides information to be considered in the strategies for similar environmental problems in the world.